Derrynaculen Connections: John Keats and Mull in the Twentieth Century. (September 2013) - Harding, Christine
Abstract : On 23 July 1818, John Keats and Charles Armitage Brown breakfasted at Derry-na-Cullen (Derrynaculen), 'the house beneath the waterfall', on the Island of Mull. At this stage of their Scottish tour they were on their way to Iona, Staffa, and Fingal's Cave. Derry-na-Cullen was abandoned in the mid-twentieth century, but still stands as an isolated ruin some miles from the main road. This essay traces what is known of the last inhabitants of that remote house, in a series of portraits and recollections as poignant in their way as Keats's short life.